TINJAUAN YURIDIS PENGAWASAN SARANA TAPPING BOX SEBAGAI WUJUD IMPLEMENTASI PERATURAN DAERAH NOMOR 6 TAHUN 2018 PERUBAHAN ATAS PERATURAN DAERAHNOMOR 6 TAHUN 2011 TENTANG PAJAK RESTORAN DI KOTA PEKANBARU - Aulia Maharani; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The implementation of restaurant tax is regulated in regional regulation No. 6 of 2018 amendment to regional regulation No. 6 of 2011 concerning restaurant tax in Pekanbaru city. In article 24 paragraph 1 it is mentioned in the supervision, the mayor or appointed official can determine personnel and or equipment, both manual and computerized systems in every restaurant tax object. Tapping box is a tool supporting the transparency of tax payments by restaurant taxpayers. But in the field there are still many business actors who do not pay taxes and do not know what and how to use tapping boxes. Therefore, it is necessary to study in a stimulant. First, the effectiveness of the use of obedience monitoring facilities for restaurant taxpayers in Pekanbaru City, second, obstacles in supervision conducted by the Pekanbaru City governmenton regional regulation number 6 year 2018 restaurant, Third, future supervision by the government Pekanbaru City against regional regulation number 6 of 2018 amendment to regional regulation no. 6 of 2011 regarding restaurant tax in Pekanbaru City.This research is a sociological legal research, because it is based on field research that is by collecting data from interview, questionnaires, and literature studies that discuss research that will help support primary, secondary and tertiary data. This study uses qualitative data analysis and produces descripitive data.From the result of the study, it was concluded that, first, the implementation of regional regulation number 6 of 2018 amendment to regional regulation number 6 of 2011 has not been running opyimally, has been carried out even distribution using tapping box in every restaurant, second, download the field talks Bapenda in the needs of taxpayers so, many businesses are paid in the form of taxes. Third, future improvements are in the form of socialization assistance, optimization of supervision and sanctions for non-compliant taxpayers. The authors suggestion is, first, to make effective use of the tapping box, second, to take advantage of the supervison of restaurant tax collection, third, are discussion of the effectiveness of the tapping box in the regional regulation specifically restaurant tax.Keywords: local regulation- controlling- restaurant tax